Possible vertical transmission and antibodies against SARS‐CoV‐2 among infants born to mothers with COVID‐19: A living systematic review. Issue 3 (10th November 2020) - Bwire, George M.; Njiro, Belinda J.; Mwakawanga, Dorkasi L.; Sabas, Deodatus; Sunguya, Bruno F.
Abstract: Current evidence suggests that coronavirus disease 2019 (COVID‐19), caused by severe respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is predominantly transmitted from human‐to‐human. However, evidence on vertical transmission and natural passive immunity among the newborns exposed to COVID‐19 is scanty and varies. This poses a challenge on preventive interventions for the newborns. We conducted a systematic review to first, determine the likelihood of vertical transmission among COVID‐19 exposed infants and second, determine whether antibodies against SARS‐CoV‐2 were generated among COVID‐19 vertically exposed but negative infants. This review registered in PROSPERO searched evidence from PubMed/MEDLINE and Google Scholar, among others. About 517 studies were pooled, where 33 articles (5.8%) met the inclusion criteria such as infection prevention and control measures at birth. A total of 205 infants born to COVID‐19 positive mothers were studied. Overall, 6.3% (13/205; 95% CI: 3.0%–9.7%) of the infants tested positive for COVID‐19 virus at birth. Of 33 eligible studies, six studies (18.8%) reported about immunoglobulin G/M (IgG/IgM) against SARS‐CoV‐2. IgG/IgM were detected in 90% infants (10/11; 95% CI: 73.9%–107.9%) who tested negative for COVID‐19 virus. The median antibody levels detected were 75.49 AU/ml (range, 7.25–140.32 AU/ml) and 3.79 AU/ml (range, 0.16–45.83 AU/ml), p  = .0041 for IgG and IgM, respectively. In conclusion, the current evidence revealed a low possibility of vertical transmission of COVID‐19 and antibodies against SARS‐CoV‐2 were detected among vertically exposed but negative infants. Further studies on transplacental transmission and the magnitude of natural passive immunity in infants born to mothers with COVID‐19 are warranted. Highlights: A systematic review was conducted to determine the likelihood of vertical transmission among COVID‐19 exposed infants and whether antibodies against SARS‐CoV‐2 were generated among COVID‐19 vertically exposed but negative infants. We found a low possibility of vertical transmission of COVID‐19 while antibodies against SARS‐CoV‐2 were detected among vertically exposed but negative infants. Further studies on vertical transmission and antibodies against COVID‐19 are warranted.